Charge, orbital, and magnetic ordering in La0.5Ca0.5MnO3 - Radaelli, P; Cox, D; Marezio, M; Cheong, S (1997)
The unusual magnetic properties of La0.5Ca0.5MnO3 were found to be associated with structural and magnetic ordering phenomena, resulting from the close interplay between charge, orbital, and magnetic ordering. Analysis of synchrotron x-ray and neutron powder diffraction data indicates that the anomalous and hysteretic behavior of the lattice parameters occurring between Tc∼225 K and TN∼ 155 K is due to the development of a Jahn-Teller (J-T) distortion of the MnO6 octahedra, the dz 2 orbitals being oriented perpendicular to the orthorhombic b axis. We observed an unusual broadening of the x-ray Bragg reflections throughout this temperature region, suggesting that this process occurs in stages. Below TN, the development of well-defined satellite peaks in the x-ray patterns, associated with a transverse modulation with q = [l/2-ε,0,0], indicates that quasicommensurate (ε∼0) orbital ordering occurs within the a-c plane as well. The basic structural features of the charge-ordered low-temperature phase were determined from these satellite peaks. The low-temperature magnetic structure is characterized by systematic broadening of the magnetic peaks associated with the "Mn+3" magnetic sublattice. This phenomenon can be explained by the presence of magnetic domain boundaries, which break the coherence of the spin ordering on the Mn+3 sites while preserving the coherence of the spin ordering on the Mn+4 sublattice as well as the identity of the two sublattices. The striking resemblance between these structures and the structural "charge ordering" and "discommensuration" domain boundaries, which were recently observed by electron diffraction and real-space imaging, strongly suggests that these two types of structures are the same and implies that, in this system, commensurate long-range charge ordering coexists with quasicommensurate orbital ordering.